Questioned document examination with the use of alternative and complementary non-destructive methods - Cieśla, Rafał (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
Questioned document examination occupies an important position in forensic science. Its purpose is to provide the authority conducting legal proceedings with reliable knowledge conﬁrming or excluding authenticity of a document, therefore every eﬀort should be made to use relevant and legally admissible examination methods. For many years reliable non-destructive methods have been developed, whose use in expert examination will enable subsequent control both by the authority conducting legal proceedings and other parties in the proceedings. This article proposes the use of alternative non-destructive methods in examination of documents.
Keywords: badanie kwestionowanego dokumentu; metody nieinwazyjne; badanie atramentu; Wizyjny Komparator Spektralny VSC2000 / HR; wideospektrokomparator; Ramanowski Komparator Spektralny FORAM 685-2; ramanspektrokomparator